2007
DOI: 10.1021/ic7006183
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Emission from Platinum(II) Complexes Intercalated into Zirconium Phosphate-Layered Materials

Abstract: The direct ion exchange of chloro(2,6-bis(N-methylbenzimidazol-2-yl)pyridine)platinum(II) ([Pt(Me(2)bzimpy)Cl]+) and chloro(2,2':6',2' '-terpyridine)platinum(II) ([Pt(tpy)Cl]+) complexes within a zirconium phosphate (ZrP) framework has been accomplished. The physical and spectroscopic properties of [Pt(Me(2)bzimpy)Cl]+ and [Pt(tpy)Cl]+ intercalated in ZrP were investigated by X-ray powder diffraction and X-ray photoelectron, infrared, absorption, and luminescence spectroscopies. In contrast to unintercalated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 60 publications
(120 reference statements)
5
35
0
Order By: Relevance
“…38 Recently, we reported that the direct ion-exchange of two monomeric platinum complexes, [Pt(Me 2 bzimpy)Cl] + (Me 2 bzimpy = 2,6-bis(N-methylbenzimidazol-2-yl)pyridine) and [Pt(tpy)Cl] + (tpy = 2,2′:6′,2″-terpyridine), into layered inorganic material zirconium phosphate (θ-ZrP) 39−42 produces novel luminescent materials. 43 Those results were consistent with an expansion of the interlayer spacing to about 18 Å to accommodate aggregates of closely interacting platinum complexes. Suspensions and powders of these intercalated materials exhibit distinct absorption and emission spectroscopic signatures characteristic of low-lying metal−metal-to-ligand charge transfer (MMLCT) states resulting from short Pt···Pt spacings.…”
Section: ■ Introductionsupporting
confidence: 67%
“…38 Recently, we reported that the direct ion-exchange of two monomeric platinum complexes, [Pt(Me 2 bzimpy)Cl] + (Me 2 bzimpy = 2,6-bis(N-methylbenzimidazol-2-yl)pyridine) and [Pt(tpy)Cl] + (tpy = 2,2′:6′,2″-terpyridine), into layered inorganic material zirconium phosphate (θ-ZrP) 39−42 produces novel luminescent materials. 43 Those results were consistent with an expansion of the interlayer spacing to about 18 Å to accommodate aggregates of closely interacting platinum complexes. Suspensions and powders of these intercalated materials exhibit distinct absorption and emission spectroscopic signatures characteristic of low-lying metal−metal-to-ligand charge transfer (MMLCT) states resulting from short Pt···Pt spacings.…”
Section: ■ Introductionsupporting
confidence: 67%
“…a-ZrP allows for intercalation of large guest molecules within the restricted interlayer space via an ion-exchange or phase-boundary mechanism, taking the advantage of the strong electrostatic interaction between the exchangeable proton and the guest molecules with positive charge. [77] Although property changes induced by the macroheterogeneous surroundings of a-ZrP have been reported on intercalation of various luminescent complexes, such as [Ru(bpy) 3 ] 2 + , [78] [Pt(tpy)Cl] + , [79] and [Re(phen)(CO) 3 Cl], [80] their prominent photocatalytic activities have scarcely been investigated to date. [81] Much effort has been dedicated to the efficient photocatalytic conversion of CO 2 into energetically beneficial molecules, such as carbon monoxide, methane, formic acid, or methanol.…”
Section: Intercalation Of Metal Complexes Within the Interlayer Spacementioning
confidence: 99%
“…The overall behaviour is consistent with the vapochromic response and electronic structures of Pt(Mebip)Cl + salts and related compounds. 47,55,56,76 The resulting emission bandshape and energy are characteristic of a lowest 3 MMLCT transition, 55,56,75 in which the excited molecule is less distorted than in the case of a more localized unimolecular MLCT state. The emission profiles are very similar for the four different blends, indicating that the emissive vapor-exposed platinum crystallites have essentially the same structures for this selection of polymers.…”
Section: Spectroscopic Studiesmentioning
confidence: 99%
“…[34][35][36] These Pt-Pt interactions can be strongly influenced by the coordinating ligand and its substituents as well as the counterion used, which can allow for tuning of the spectroscopic properties. [37][38][39][40] Studies involving the use of platinum complexes with either terpyridine [41][42][43][44][45] or 2,6-bis(benzimidazol-2 0 -yl)pyridine 46,47 have gained interest largely as a consequence of their tendency to exhibit strong photoluminescence originating from their lowest excited states having significant ligand charge-transfer and/or metal-toligand charge-transfer character. The absorption and emission properties of these complexes typically are quite sensitive to external stimuli in solution and as solids.…”
Section: Introductionmentioning
confidence: 99%